Effect of nanoscale zero-valent iron (NZVI) on bacterial viability : roles of growth phases and oxidative stress - Krittanut Chaithawiwat (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010